The Trade-off between Cost and Environmental Performance in the Presence of Sustainable Supply Chain - Sudawan Somjai; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
The foremost objective of the current study is examining the trade-off between environmental performance and cost performance in the presence of the sustainable supply chain. In particular the study has examined the impact of sustainable supply chain implantations namely sustainable procurement, sustainable distribution, sustainable production and sustainable reserve logistic on the cost and environmental performance. The study has broached the argument that the financial performance and profitability of a firm can be enhanced using SSCM activities or not. Research is limited in the context of developing economies. However, extensive research is available on developed economies. It is considerable to know about the influence of SSCM initiatives on the production sustainability in the developing countries. There is need to understand the relation between performance and SSCM initiatives among the firms in developing regions including Indonesia. There is need for creating a balance between economy and environment in these economies. Employing the survey-based methodology, the PLS-SEM technique is used to test the hypothesized relationships. So, current study has used PLS-SEM as statistical tool to answer the research questions raised in this study and research objectives envisaged in the current study. The findings of the study have provided support to the theoretical foundation and proposed hypothesis of the current study. Current study will be helpful for policymakers and practitioners in understanding the issues related to sustainable supply chain implementation and supply chain performance. In author knowledge this is among very few pioneering studies on this issue.